Effect of Health Education Using Audiovisual Media on Level of Knowledge about Leucorrhea (Fluor Albus) - Eka Noviyanti; Sunanto; Iis Hanifah (Health and Technology Journal (HTechJ), 2023)
Health education is an important issue that needs attention from all parties. The problem women often face regarding reproductive health is vaginal discharge. Leucorrhea is discharge or discharge from the vagina that is not blood. Leucorrhea is normal and abnormal. Normal vaginal discharge is characterized by a clear to whitish color, odorless and itchy, while abnormal vaginal discharge is characterized by a yellow to greenish color, smells, and causes itching. This study aims to analyze the effect of Health Education on the level of knowledge of young women about vaginal discharge. The research design used the pre-experimental method with one group pretest and post-test design. The sampling technique used is total sampling. The number of samples in this study was 40 adolescents. Data were collected using questionnaires and then analyzed using the Wilcoxon test. Based on the Wilcoxon test analysis results, the p-value was 0.001. The conclusion of this study showed that there was an effect of health education on the level of knowledge of young women about vaginal discharge (fluor albus). Health workers are expected to evaluate and conduct early education for young women regarding vaginal discharge (fluor albus) to prevent abnormal vaginal discharge (pathological fluor albus) so that they can improve the quality of health, especially in reproductive health.